Lactobacilli-host interactions inhibit Staphylococcus aureus and Escherichia coli-induced cell death and invasion in a cellular model of infection - Kiousi, Despoina Eugenia; Panopoulou, Maria; Pappa, Aglaia; Galanis, Alex (Frontiers in Microbiology, 2024)
Probiotic lactobacilli exert antimicrobial and antibiofilm activity through a plethora of mechanisms, including the production of inhibitory compounds and competition for nutrients and adhesion sites on the host mucosa. Their ability to interfere with pathogen-host interactions may mitigate the harmful effects of infection. Lactiplantibacillus pentosus L33 (L33) and Lactiplantibacillus plantarum L125 (L125) are two potential probiotic lactic acid bacteria (LAB) strains, previously shown to reduce pathogen viability and biofilm formation in vitro. The present study aims to investigate their ability to limit cell death induced by Staphylococcus aureus and Escherichia coli in the human colon adenocarcinoma cell line HT-29. To this end, we examined the protective effects of the two strains using in silico, in vitro and omic approaches, with Lacticaseibacillus rhamnosus GG (LGG) serving as a reference strain, due to its well-documented antimicrobial properties. Based on the findings of our study, direct contact of HT-29 cells with L125 for 4 h prior to the addition of S. aureus or E. coli prevented pathogen-induced cell death at rates comparable to LGG. In contrast, L33 failed to exert a protective effect. Moreover, L125 significantly reduced adherence of S. aureus to HT-29 cells, and the internalization capacity of both pathogens (>1.5 Log CFU/mL). Dual RNA-seq and protein microarrays were used to determine expression changes in L125 and host cells during co-incubation. L125 expressed high levels of adhesins and moonlighting proteins, homologous to those encoded by the pathogens. Pathways involved in pathogen adhesion and internalization, endocytosis, cell–cell and cell-extracellular matrix (ECM) adhesion, were downregulated in HT-29 cells. Finally, L125 reduced the secretion of various pro-inflammatory mediators. Our findings highlight the strain-specific protective effects of LAB against pathogen-induced cell death achieved through competitive exclusion and priming of host cell responses. Future studies will focus on elucidating the specific surface components of L125 involved in these events, paving the way for targeted interventions at the host-pathogen interface.